2004
DOI: 10.1083/jcb.200405148
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes-linked transcription factor PAX4 promotes β-cell proliferation and survival in rat and human islets

Abstract: The mechanism by which the β-cell transcription factor Pax4 influences cell function/mass was studied in rat and human islets of Langerhans. Pax4 transcripts were detected in adult rat islets, and levels were induced by the mitogens activin A and betacellulin. Wortmannin suppressed betacellulin-induced Pax4 expression, implicating the phosphatidylinositol 3-kinase signaling pathway. Adenoviral overexpression of Pax4 caused a 3.5-fold increase in β-cell proliferation with a concomitant 1.9-, 4-, and 5-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
127
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 55 publications
14
127
1
4
Order By: Relevance
“…Our proliferation results with MIN6 cells are also consistent with another study that showed an approximately threefold increase in proliferation of primary rat beta cells treated with activin A [47]. Collectively, activin A and follistatin appear to modulate the maturation state of adult beta cells, with activin A driving mature beta cells to a more progenitor-like phenotype with increased proliferation and decreased differentiated function.…”
Section: Discussionsupporting
confidence: 90%
“…Our proliferation results with MIN6 cells are also consistent with another study that showed an approximately threefold increase in proliferation of primary rat beta cells treated with activin A [47]. Collectively, activin A and follistatin appear to modulate the maturation state of adult beta cells, with activin A driving mature beta cells to a more progenitor-like phenotype with increased proliferation and decreased differentiated function.…”
Section: Discussionsupporting
confidence: 90%
“…Cells were then stained with DAPI (4′,6-diamidino-2-phenylindole) to reveal the nuclei and mounted using Dako fluorescent mounting medium. Proliferation was measured by BrdU incorporation as described previously [35].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Il serait alors envisageable de développer des agents pharmacologiques activateurs de Pax4 pour stimuler in vivo la prolifération des cellules β et compenser ainsi leur perte pathologique. Nous avons pu confirmer le rôle fondamental de Pax4 dans la cellule β [9]. En effet, les facteurs de croissance, activine A et β-celluline (membres respectivement de la famille des transforming growth factors et epidermal growth factors), stimulent l'expression du gène pax4 et la prolifération des cellules β dans les îlots de rat.…”
unclassified
“…La surexpression constitutive de Pax4 dans les îlots de rat au moyen d'adénovirus recombinants induit une augmentation de la réplication des cellules β qui, normalement, prolifèrent peu à l'âge adulte (Figure 1 La prolifération (anti-BrdU, en jaune), l'expression de l'insuline (anti-insuline, en rouge) et les noyaux (DAPI, en bleu) sont détectés par immunofluorescence dans les cellules β d'îlots de rat dispersés, puis infectés avec des adénovirus codant pour la protéine β-galactosidase (témoin, A) ou le facteur de transcription Pax4 (B). Une augmentation de la réplication est observée dans les cellules surexprimant Pax4 (d'après [9]). du facteur de transcription c-myc, ainsi que celui de son gène cible Id2, sont augmentés, identifiant ainsi la voie cmyc/Id2 comme médiatrice entre Pax4 et la réplication cellulaire [9].…”
unclassified
See 1 more Smart Citation